Progress in Thin Film Solar Cells Based on Cu2ZnSnS4 - Hongxia Wang (International Journal of Photoenergy)
The research in thin film solar cells has been dominated by light absorber materials based on CdTe and Cu(In,Ga)Se2 (CIGS) in the last several decades. The concerns of environment impact of cadmium and the limited availability of indium in those materials have driven the research towards developing new substitute light absorbers made from earth abundant, environment benign materials. Cu2ZnSnS4 (CZTS) semiconductor material has emerged as one of the most promising candidates for this aim and has attracted considerable interest recently. Significant progress in this relatively new research area has been achieved in the last three years. Over 130 papers on CZTS have been published since 2007, and the majority of them are on the preparation of CZTS thin films by different methods. This paper, will review the wide range of techniques that have been used to deposit CZTS semiconductor thin films. The performance of the thin film solar cells using the CZTS material will also be discussed.